Molecular Dissection of a Conserved Cluster of miRNAs Identifies Critical Structural Determinants That Mediate Differential Processing - Pandey, Manish; Luhur, Arthur; Sokol, Nicholas S.; Chawla, Geetanjali (Frontiers in Cell and Developmental Biology, 2022)
Differential processing is a hallmark of clustered microRNAs (miRNAs) and the role of position and order of miRNAs in a cluster together with the contribution of stem-base and terminal loops has not been explored extensively within the context of a polycistronic transcript. To elucidate the structural attributes of a polycistronic transcript that contribute towards the differences in efficiencies of processing of the co-transcribed miRNAs, we constructed a series of chimeric variants of Drosophila let-7-Complex that encodes three evolutionary conserved and differentially expressed miRNAs (miR-100, let-7 and miR-125) and examined the expression and biological activity of the encoded miRNAs. The kinetic effects of Drosha and Dicer processing on the chimeric precursors were examined by in vitro processing assays. Our results highlight the importance of stem-base and terminal loop sequences in differential expression of polycistronic miRNAs and provide evidence that processing of a particular miRNA in a polycistronic transcript is in part determined by the kinetics of processing of adjacent miRNAs in the same cluster. Overall, this analysis provides specific guidelines for achieving differential expression of a particular miRNA in a cluster by structurally induced changes in primary miRNA (pri-miRNA) sequences.